2020
DOI: 10.47408/jldhe.vi18.571
|View full text |Cite
|
Sign up to set email alerts
|

A learning development-faculty collaborative exploration of postgraduate research student mental health in a UK university

Abstract: Mental ill-health is an escalating problem in higher education. Not only does this impact students’ ability to learn, it can lead to poor completion, with learners opting to withdraw from studies, even if attainment has been satisfactory. The aim of this study was to gain insight about perceptions of poor mental health from postgraduate research students in a diverse UK university and canvas opinion regarding how the University could improve this. A short, pragmatic survey with basic quantitative and qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Even though some studies have reported on the literature in different subject fields, there have been no bibliometric studies explicitly conducted on graduate students' mental health and well-being. Quantitative surveys have been undertaken on Economics graduate students' mental health [16], the mental health crisis in graduate education [14], the link between mental health and doctoral students [15], experiences of belonging in relation to mental health and well-being [36], and the perceptions on and assessment of mental health [37,38]. Another study used critical self-reflections on postgraduate researchers' mental health and well-being [39].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Even though some studies have reported on the literature in different subject fields, there have been no bibliometric studies explicitly conducted on graduate students' mental health and well-being. Quantitative surveys have been undertaken on Economics graduate students' mental health [16], the mental health crisis in graduate education [14], the link between mental health and doctoral students [15], experiences of belonging in relation to mental health and well-being [36], and the perceptions on and assessment of mental health [37,38]. Another study used critical self-reflections on postgraduate researchers' mental health and well-being [39].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This is particularly relevant in the current project, where participants were not referred to participate within a health context, but rather, self-nominated to join the program in order to grapple with a challenge they were facing. Although research into the mental health of PhD researchers suggests that several of them may have also been diagnosed with mental ill health (Delderfield et al, 2020;Naumann et al, 2022), this was not the participant's focus and therefore it was important not to pathologise their attempts at self-care.…”
Section: Emphasising External Conditions As Well As Personal Experiencesmentioning
confidence: 99%
“…Additionally, a major limitation of the online medium is the reduced non-verbal communication resulting in less efficient communication, potential frustration, and disruption to wellbeing monitoring during one-to-one LD tutorials (Delderfield et al, 2020).…”
mentioning
confidence: 99%